Low-cost voltammetric sensor based on reduced graphene oxide anchored on platinum nanoparticles for robust determination of Favipiravir in real samples - TIRIS, GİZEM; Bouali W.; ERK N.; Kholafazadehastamal G.; Naser M.; TIRIS G. (My University, 2023)
© 2022 Elsevier B.V.This research describes a simple, sensitive, and disposable modified glassy carbon electrode constructed using platinum nanoparticles anchored on reduced graphene oxide nanocomposite as a conductive modifier (Pt@rGO/GCE) to detect an anti-coronavirus drug, Favipiravir (FAV). The as-synthesized nanocomposite was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), and atomic force microscopy (AFM). Under optimized conditions, the square wave voltammetry (SWV) method was used to determine trace amounts of FAV in real samples. The proposed electrode demonstrated a wide linear concentration range of 3.16 to 100.0 μM with a low detection limit (LOD) of 2.46 μM. Moreover, the developed electrode showed outstanding selectivity in the presence of several interferences with high repeatability and reproducibility. Finally, the developed electrode was applied to detect FAV in human plasma and pharmaceutical samples.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; FİZİK, YOĞUN MADDE; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; PHYSICS; ENGINEERING, MECHANICAL; ENGINEERING, ELECTRICAL & ELECTRONIC; PHYSICS, CONDENSED MATTER; MATERIALS SCIENCE, MULTIDISCIPLINARY; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Genel Kimya; Makine Mühendisliği; Malzeme Kimyası; Elektrik ve Elektronik Mühendisliği; Electronic, Optical and Magnetic Materials; Physical Sciences; General Chemistry; Mechanical Engineering; Materials Chemistry; Electrical and Electronic Engineering; Covid-19; Favipiravir; Graphene oxide; Metal nanoparticles; Pharmaceutical sample